Quantification of Biventricular Strains in Heart Failure With Preserved Ejection Fraction Patient Using Hyperelastic Warping Method - Zou, Hua; Xi, Ce; Zhao, Xiaodan; Koh, Angela S.; Gao, Fei; Su, Yi; Tan, Ru-San; Allen, John; Lee, Lik Chuan; Genet, Martin; Zhong, Liang (Frontiers in Physiology, 2018)
Heart failure (HF) imposes a major global health care burden on society and suffering on the individual. About 50% of HF patients have preserved ejection fraction (HFpEF). More intricate and comprehensive measurement-focused imaging of multiple strain components may aid in the diagnosis and elucidation of this disease. Here, we describe the development of a semi-automated hyperelastic warping method for rapid comprehensive assessment of biventricular circumferential, longitudinal and radial strains that is physiological meaningful and reproducible. We recruited and performed cardiac magnetic resonance (CMR) imaging on 30 subjects (10 HFpEF, 10 heart failure with reduced ejection fraction patients (HFrEF) and 10 healthy Controls). In each subject, a three-dimensional heart model including left ventricle (LV), right ventricle (RV) and septum was reconstructed from CMR images. The hyperelastic warping method was used to reference the segmented model with the target images and biventricular circumferential, longitudinal and radial strain-time curves were obtained. The peak systolic strains are then measured and analyzed in this study. Intra- and inter-observer reproducibility of the biventricular peak systolic strains was excellent with all ICCs>0.92. LV peak systolic circumferential, longitudinal and radial strain, respectively, exhibited a progressive decrease in magnitude from healthy Control → HFpEF→ HFrEF: Control (-15.5±1.90%, -15.6±2.06%, 41.4±12.2%); HFpEF (-9.37±3.23%, -11.3±1.76%, 22.8±13.1%); HFrEF (-4.75±2.74%, -7.55±1.75%, 10.8±4.61%). A similar progressive decrease in magnitude was observed for RV peak systolic circumferential, longitudinal and radial strain: Control (-9.91±2.25%, -14.5±2.63%, 26.8±7.16%); HFpEF (-7.38±3.17%, -12.0±2.45%, 21.5±10.0%); HFrEF (-5.92±3.13%, -8.63±2.79%, 15.2±6.33%). Furthermore, septum peak systolic circumferential, longitudinal and radial strain magnitude decreased gradually from healthy Control to HFrEF: Control (-7.11±1.81%, 16.3±3.23%, 18.5±8.64%); HFpEF (-6.11±3.98%, -13.4±3.02%, 12.5±6.38%); HFrEF (-1.42±1.36%, -8.99±2.96%, 3.35±2.95%). The ROC analysis indicated LV peak systolic circumferential strain to be the most sensitive marker for differentiating HFpEF from healthy Controls. Our results suggest that the hyperelastic warping method with the CMR-derived strains may reveal subtle impairment in heart failure biventricular mechanics, in particular despite a “normal” ventricular ejection fraction in HFpEF.